Sensorineural correlates of failed functional recovery after natural regeneration of vestibular hair cells in adult mice - Jáuregui, Emmanuel J.; Scheinman, Kelli L.; Bibriesca Mejia, Ingrid K.; Pruett, Lindsay; Zaini, Hannah; Finkbeiner, Connor; Phillips, Jonathan A.; Gantz, Jay A.; Nguyen, Tot Bui; Phillips, James O.; Stone, Jennifer S. (Frontiers in Neurology, 2024)
Vestibular hair cells (HCs) are mechanoreceptors that sense head motions by modulating the firing rate of vestibular ganglion neurons (VGNs), whose central processes project to vestibular nucleus neurons (VNNs) and cerebellar neurons. We explored vestibular function after HC destruction in adult Pou4f3+/DTR (DTR) mice, in which injections of high-dose (50 ng/g) diphtheria toxin (DT) destroyed most vestibular HCs within 2 weeks. At that time, DTR mice had lost the horizontal vestibulo-ocular reflex (aVORH), and their VNNs failed to upregulate nuclear cFos expression in response to a vestibular stimulus (centrifugation). Five months later, 21 and 14% of HCs were regenerated in utricles and horizontal ampullae, respectively. The vast majority of HCs present were type II. This degree of HC regeneration did not restore the aVORH or centrifugation-evoked cFos expression in VNNs. The failure to regain vestibular pathway function was not due to degeneration of VGNs or VNNs because normal neuron numbers were maintained after HC destruction. Furthermore, sinusoidal galvanic stimulation at the mastoid process evoked cFos protein expression in VNNs, indicating that VGNs were able to regulate VNN activity after HC loss. aVORH and cFos responses in VNNs were robust after low-dose (25 ng/g) DT, which compared to high-dose DT resulted in a similar degree of type II HC death and regeneration but spared more type I HCs in both organs. These findings demonstrate that having more type I HCs is correlated with stronger responses to vestibular stimulation and suggest that regenerating type I HCs may improve vestibular function after HC loss.